De la philosophie à l'école à une école philosophique. Redonner de la saveur aux savoirs pour lutter contre les inégalités scolaires - Edwige Chirouter (Éducation et Socialisation)
The introduction of philosophy from a very early age, for the most part, goes beyond the need to democratise access to this academic discipline and therefore questions of didactics. The practice questions the very meaning of passing on knowledge and the fundamental definition of the purpose of schooling. We therefore make the hypothesis that, in our interdisciplinary experiments, a philosophical approach to knowledge may give more meaning to academic activities. Therefore, your strong hypothesis is that a philosophical approach would lead to a rediscovery of the “saveurs” of knowledge, to take up J-P. Astolfi’s expression (2008). By questioning the meaning and epistemological status of knowledge students can bring forth once more the concerns and questions that gave rise to human knowledge. They can, perhaps, better understand the epistemological challenges of taught knowledge and, in some cases, change their relationship with knowledge for the better.